RICH SOURCE OF NEUTRACEUTICLE: CUCUMIS SATIVUS (CUCUMBER) - V. Changade, Jayashree.; Ulemale, Anil H. (International Journal of Ayurveda and Pharma Research, 2015)
Cucumber (Cucumis Sativus) belongs to Cucurbitaceae family which is abundantly found in India. It is widely cultivated plant. The fruit is used as supplementary to principal food components & also Medicine since ages. Its Diuretic function is well known and it is systematically described in Charak and Sushrut samhita. According to its stages, its different properties are described. Cucumis Sativus is economic and rich in carbohydrates, proteins, fibres, vitamins mainly A, B1, B2, B6, C, D, E, macro nutrients like Na, K, Ca and micro nutrients such as Cu, Ze, Fe. In addition to this, the plant has many phyto constituents like glycosides, flavones, terpenoids, phytosterol, saponine and carotene B. Fruit can be used in the form of conc. juice, slices (slices dried or fresh). It helps to promote health and cure diseases. Its fresh fruit is rich source of moisture. It can be used in place of mineral water for oral rehydration. It needs to be used in preparing sqash, jam and jelly. It is also used in various cosmetics due to its high moisture content. Malnutrition is worldwide problem. Cucumber is easily available, affordable and fulfils requirements of micro & macronutrients in the body. Therefore, Cucumber can be used as food supplement in the malnutrition areas. Adulteration in synthetic food and its side effects is one of the serious health related issue. Use of Cucumber as supplementary to food helps to overcome these problems.